Being feminist, being Christian : essays from academia - Julé, Allyson, 1965-; Pedersen, Bettina Tate (Palgrave Macmillan, 2006)
This collection of eight extended essays explores the various intersections of feminism, feminist theory and practice, and Christian tradition as it is lived out in the lives of Christian academics. The basic question informing this volume is "Can a person be Christian and feminist at the same time?" The authors aim to demonstrate that a person can, and go on to illustrate the various ways current thinkers are working this out. This collection is unique in its gathering of Christian perspectives from both Catholic and Protestant traditions.